Можемо ли трансплантацијом јетре смањити оксидативни стрес? оксидативни стрес у цирози и након трансплантације - Aydin, Mesut (Journal of Medical Biochemistry, 2021)
Background: The aim of this study was to determine the levels of lipid peroxidation (MDA) and antioxidants such as reduced glutathione (GSH), catalase (CAT) and superoxide dismutase (SOD) in the blood serum of patients with cirrhosis and liver transplantation.Materials and Methods: In this study, serum malondialdehyde acid (MDA) levels, superoxide dismutase (SOD), reduced glutathione (GSH), and catalase (CAT) activities were measured spectrophotometrically and compared to the results of the healthy control group.Results: SOD, CAT and GSH activities were significantly decreased in the patient groups compared to the healthy control group (p
Keywords: оксидативни стрес, цироза, трансплантација јетре